Including externalities in the costs analysis of bus fleet: a case study - Emiliano, William Machado (2017)
Public transportation is fundamental to ensure quality of life to the population allowing to deal with the environmental challenges of the sector. However, public transportation also promotes a number of problems and impacts, such as Greenhouse Gas (GHG) emissions, noise pollution, accidents and congestion. The importance of the public transportation sector in Brazil is also evident. This research aimed to design and implement a methodology to consider externalities in the costs analysis of bus fleets. The case of Joinville city in Santa Catarina State, Brazil was used to compare different bus technological options to respond to the needs for public transport on three different routes. The TCwE (Total Cost with externalities) model was proposed and tested for these cases considering diesel, electric, compressed natural gas, bioethanol, hydrogen and hybrid buses. The results show that externalities can affect decision making in the choice of a bus fleet. For the case under study, the best option is a fleet composed of hybrid buses, due to its low operating costs, maintenance and externalities.